BETWEEN KINGS, TRUTHS AND VEILS: A (PROBABLE) ILLUSION OF PURE PROCEDURAL JUSTICE - Bruno da Silva, Alexandre Antônio; Brunetta, Cintia (Revista Inclusiones, 2021)
This article aims to describe, in a perfunctory way, the theories related to procedural justice of John Rawls and Jürgen Habermas, confronting them with the recent discoveries brought by neuroscience. For this, a brief summary of parts of the work of these philosophers will be made, specifically seeking to isolate the rational element required in both theories. Afterwards, it will be tried to deconstruct the notion of modern rationality included in them, from brief considerations about the Herbert Simon’s concept of limited rationality. Following, it will be shown the search of how man is deceived from the senses and and how this limited cognition of reality affects political decisions. Finally, by way of a conclusion, it will be suggested the need to (re) visit the theories of John Rawls and Jürgen Habermas with the tools provided by the new studies of human mind and rationality